Platform Monitoring Berbasis Web untuk Sistem Stabilitas dan Pelacakan Kapal Nelayan - Tedyyana, Agus; Ratnawati, Fajar; Danuri, Danuri (Digital Zone: Jurnal Teknologi Informasi dan Komunikasi, 2023)
Fishing activities in the waters of Bengkalis Island face a number of serious problems, including a lack of data during fishing activities and ship accidents caused by delays in information. In response to this problem, this research proposes the development of a "Web-Based Monitoring Platform for the Stability and Tracking System for Fishing Vessels on Bengkalis Island", or also known as the SMARST tool. Safety is the top priority. SMARST is equipped with an early warning system that uses predictive algorithms to identify potential dangers, such as bad weather conditions. If an emergency occurs, fishermen can immediately contact the authorities via the integrated emergency communications facility. This tool is designed to monitor fishing activities, including monitoring the safety of ships when operating at sea. The implementation of the SMARST tool is expected to increase the success of fishing activities at sea and ensure the safety of fishermen and their vessels. This innovation offers an integrated solution to support the sustainability and efficiency of the fishing industry on Bengkalis Island. The SMARST tool will be able to identify the location of vessels in real-time, ensure their safety from threats such as conflicts with Malaysian authorities and assist in mitigating the risk of accidents. The system was built using an Agile approach, which allows for iterative development and is responsive to user needs. Key functionalities of SMARST include real-time tracking of vessel locations, monitoring vessel conditions, and providing the latest information relevant to fishing activities. From a non-functional perspective, this system emphasizes reliability, ease of use, and scalability.